Author Response: Trajectories of Neurologic Recovery 12 Months After Hospitalization for COVID-19: A Prospective Longitudinal Study. (3rd January 2023) - Frontera, Jennifer
Abstract : We appreciate the interest in our study. 1 The reader points out important pathophysiologic concerns that pertain to SARS-CoV-2, acute brain injury, and cognitive sequelae. Several studies in animal models and humans have identified cytokine/chemokine elevations acutely after SARS-CoV-2 infection, which can lead to disruption of the endothelium in cerebral microvessels with subsequent microthrombus formation and microhemorrhages, along with activation of the complement cascade. 2 Downstream parenchymal microglial and astrocyte activation can lead to additional cytokine/chemokine release and eventual neuronophagia. 3